Nabil Sobhi Hanna’s Contributions To The Establishment Of Medical Anthropology In The Arab World - Bensafi , Samira (Migration Letters, 2024)
The history of medical anthropology as a subfield of anthropological studies dates back to the fifties of the last century, although the history of the reciprocal relationship between medicine and anthropology dates back to the nineteenth century, the beginning of prosperity was when medical anthropology contributed to the study of medical problems with the end of World War II, and through this article, we will introduce the reader to this scientific branch by the scientific branch, that is to say medical anthropology in the Arab world through presenting his scientific curriculum and his diploma in Arab and European universities, up to his scientific production.